Water supply and sewerage: sector working paper - World Bank (Washington D.C. World Bank, 1971)
The purpose of this paper is to elaborate on one dimension of the urban problems in developing countries - the need for adequate water and sewerage facility
osc 01/02/2019
Loans
Keywords: Water supply